Comparative leaf architectural studies of some Vernonia SCHREB (Asteraceae) in Nigeria - Aworinde, David Olaniran; Ogundairo, Bushirat Odunayo; Erinoso, Sakiru Morenikeji (Current Botany, 2013)
Abstract